Hypofractionation and prostate cancer: A good option for Africa? - Luca Incrocci; Ben Heijmen; Patrick Kupelian; Hannah M. Simonds (South African Journal of Oncology, 2017)
Cancer is an emerging public health problem in Africa. According to the World Health Organization, the numbers will be doubled by 2030 because of the ageing and the growth of the population. Prostate cancer is the most common cancer among men in most African countries. Radiotherapy machines are extremely limited in Africa and therefore prostate cancer in Africa is mostly managed by urologists. However, for a large proportion of prostate cancer patients, external-beam radiotherapy (EBRT) will be the treatment of choice in Africa because of limitations of surgical expertise in many countries. The disparity between the α/β ratio for late complications and the low α/β ratio for prostate cancer widens the therapeutic window when treating prostate cancer with hypofractionation. Because of the reduced number of treatment days, hypofractionation offers economic and logistic advantages, reducing the burden of the very limited radiotherapy resources in most African countries. It also increases patient convenience. A misleading assumption is that high-level radiotherapy is not feasible in low-income countries. The gold standard option for hypofractionation includes daily image-guided radiotherapy with 3–4 implanted gold fiducials. Acceptable methods for image guidance include ultrasound and cone-beam computed tomography (CT). CT-based treatment planning with magnetic resonance imaging fusion allows for accurate volume delineation. Volumetric modulated arc therapy or inversely planned intensity modulated radiotherapy is the ideal for treatment delivery. The most vital component is safe delivery, which necessitates accurate quality assurance measures and on-board imaging. We will review the evidence and potential utilisation of hypofractionated EBRT in Africa.